Morphological and Molecular Diversification of Asian Endemic Difflugia tuberspinifera (Amoebozoa, Arcellinida): A Case of Fast Morphological Evolution in Protists? - Gomaa, Fatma; Yang, Jun; Mitchell, Edward; Zhang, Wen-Jing; Yu, Zheng; Todorov, Milcho; Lara, Enrique (My University, 2015)
Planktonic arcellinid testate amoebae exhibit a broad-range of morphological variability but it is currently unclear to what extent this variability represents phenotypic plasticity or if it is genetically determined. We investigated the morphology and phylogenetic relationships of three endemic east-asian Difflugia taxa 1) the vase-shaped D. mulanensis, 2) and a spinose and a spineless morphotypes of D. tuberspinifera using scanning electron microscopy and two ribosomal genetic markers (SSU rDNA and ITS sequences). Our phylogenetic analyses shows that all three taxa are genetically distinct and closely related to D. achlora and Netzelia oviformis. The genetic variations between the spineless and spinose morphotypes of D. tuberspinifera were low at the SSU rRNA level (0.4%), but ten times higher at the ITS level (4.5-6%). Our data suggest that the two forms of D. tuberspinifera are sufficiently differentiated in terms of morphology and genetic characteristics to constitute two separate entities and that the presence of spines does not result from phenotypic plasticity due to environmental selective pressure. However further observational and experimental data are needed to determine if these two forms constitute different biological species.
Keywords: Molecular phylogeny; SSU rRNA gene; ITS; Difflugia tuberspinifera; morphological variation; fast evolution; China